Spatial-temporal Analysis Distribution of Buildings Martapura River Border in Banjarmasin City - Muhaimin, Muhammad; Aristin, Nevy Farista; Kamil, Ahmad; Adyatma, Sidharta; Saputra, Aswin Nur (Faculty of Geography, Universitas Gadjah Mada, 2025)
The role of the people of Banjarmasin City has long made the river a center of activity that has a ‎dependence on river culture as a way of life, behavior, and adaptation the river boundary for ‎generations, including the construction of buildings. This activity has an impact on the ‎uncontrollability of buildings. And the function of the river. The study aimed to assess the ‎extent of the distribution and non-conformity of buildings with river boundary regulations stipulated in Banjarmasin City Regional Regulation No. 31/2012 concerning the Determination of ‎Regulation and Utilization of Rivers and Former Rivers. The method used is descriptive quantitative ‎with spatial analysis techniques on visual image interpretation and river area buffering within 15 ‎meters of the left and right banks of the river. Data analysis used an overlay technique to determine the ‎number of buildings within the Martapura River boundary line in Banjarmasin City. The results showed ‎that, over 15 years from 2008 to 2023, the built-up land area changed by an average of 1.30 hectares. Based on the type of built-up land, the most dominant is residential buildings. Non-conforming buildings in 2008 totaled 3,518 buildings, in 2013 totaled 3,365 buildings, in 2018 totaled ‎‎3,321 buildings, and in 2023 totaled 3,301 buildings. The decrease in non-conforming buildings ‎occurred periodically in Central Banjarmasin District, and the increase in the number of non-conforming buildings was spread in South Banjarmasin District and North Banjarmasin District‎.Received: 2024-10-01 Revised: 2025-11-10 Accepted: 2025-12-11 Published: 2025-12-22